Dietary Diversity Score and Nutritional Status of Adolescent Girls with Anemia in Bandung Region - Astuti, Widya; Prameswari, Fajria Saliha Puspita; Rosdiana, Delita Septia; Fauza, Ahdiyatul; Insani, Hurry Mega (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study aimed to determine the association between Dietary Diversity Scores (DDS) and nutritional status among adolescent girls with anemia. Seventy-one adolescent girls aged 15−17 years from high schools in Bandung were selected using Probability Proportional to Size (PPS). The data on the sociodemographic characteristics, health and nutritional status, and DDS of the subjects were collected. Results showed that the mean DDS was classified as high. There was no significant association between DDS and BMI-for-age Z-score (BAZ) and Waist-Hip Ratio (WHR) in adolescent girls with anemia (p>0.05). Therefore, DDS was not associated with nutritional status in adolescent girls with anemia.